Analisis Risiko Ergonomi Dan Karakteristik Pekerja Dengan Keluhan Subjektif Musculoskeletal Disorders Pada Pekerja Industri Manufaktur - Bryan Novianjaya Putra; Zulfia Maharani; Wakhyono Budianto (BULLET : Jurnal Multidisiplin Ilmu, 2025)
Musculoskeletal Disorders (MSDs) or complaints in the musculoskeletal system are complaints in parts of the skeletal muscles that are felt by a person ranging from very mild complaints to very painful. Based on the British Medical Journal report, there were around 322.75 million cases of accidents, deaths and disability-adjusted life years in 2019 caused by MSDs. This study aims to determine the level of ergonomic risk and individual characteristics that cause subjective complaints of Musculoskeletal Disorders (MSDs) in PT workers. Indoporlen Refractories. The population and sample for this study were all maintenance workers, totaling 11 people. This research is a descriptive analytical study with an observational approach using a cross sectional study design, namely to observe and measure the level of ergonomic risk and individual characteristics of workers which are the independent variables, as well as complaints of Musculoskeletal Disorders (MSDs) as the dependent variable. The results of this research analysis show that there is a significant relationship between the level of ergonomic risk and subjective complaints of Musculoskeletal Disorders (MSDs) (p value = 0.026) and worker characteristics with subjective complaints of Musculoskeletal Disorders (MSDs) based on age (p value = 0.036) and length of service (p value = 0.022).